Belize : Assessment of the Supervision and Regulation of the Financial Sector-Review of Financial Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2004)
This paper highlights key finding of the assessment of financial sector regulation and supervision in Belize. The assessment reveals that banking supervision in Belize complies with or is largely compliant with most of the Basel Core Principles. Under current arrangements, the Minister retains a good deal of discretionary authority with respect to banking supervision, but this situation is likely to be modified if a draft bill, now under discussion, becomes law. Retention of qualified staff is a continuous problem with the result that the intensity of banking supervision varies.